Tomato Domestication Attenuated Responsiveness to a Beneficial Soil Microbe for Plant Growth Promotion and Induction of Systemic Resistance to Foliar Pathogens - Jaiswal, Amit K.; Mengiste, Tesfaye D.; Myers, James R.; Egel, Daniel S.; Hoagland, Lori A. (Frontiers in Microbiology, 2020)
Crop domestication events followed by targeted breeding practices have been pivotal for improvement of desirable traits and to adapt cultivars to local environments. Domestication also resulted in a strong reduction in genetic diversity among modern cultivars compared to their wild relatives, though the effect this could have on tripartite relationships between plants, belowground beneficial microbes and aboveground pathogens remains undetermined. We quantified plant growth performance, basal resistance and induced systemic resistance (ISR) by Trichoderma harzianum, a beneficial soil microbe against Botrytis cinerea, a necrotrophic fungus and Phytophthora infestans, a hemi-biotrophic oomycete, in 25 diverse tomato genotypes. Wild tomato related species, tomato landraces and modern commercial cultivars that were conventionally or organically bred, together, representing a domestication gradient were evaluated. Relationships between basal and ISR, plant physiological status and phenolic compounds were quantified to identify potential mechanisms. Trichoderma enhanced shoot and root biomass and ISR to both pathogens in a genotype specific manner. Moreover, improvements in plant performance in response to Trichoderma gradually decreased along the domestication gradient. Wild relatives and landraces were more responsive to Trichoderma, resulting in greater suppression of foliar pathogens than modern cultivars. Photosynthetic rate and stomatal conductance of some tomato genotypes were improved by Trichoderma treatment whereas leaf nitrogen status of the majority of tomato genotypes were not altered. There was a negative relationship between basal resistance and induced resistance for both diseases, and a positive correlation between Trichoderma-ISR to B. cinerea and enhanced total flavonoid contents. These findings suggest that domestication and breeding practices have altered plant responsiveness to beneficial soil microbes. Further studies are needed to decipher the molecular mechanisms underlying the differential promotion of plant growth and resistance among genotypes, and identify molecular markers to integrate selection for responsiveness into future breeding programs.